Ethno-Religious Heritage of Former Eastern Territories of the Polish-Lithuanian Commonwealth in Contemporary Poland - Rykała, Andrzej (European Spatial Research and Policy, 2013)
The main objective of this paper is to present the national and religious heritage of the Eastern Borderlands in contemporary Poland. The paper deals with the genesis and selected aspects of the spatial development of the ethnic and religious minorities (mainly Tartars-Muslims, Karaites and Armenians) that date back to the eastern areas of the former Republic (including the territories of Belarus, Lithuania and Ukraine) but, due to the post-war border changes and migrations, formed clusters in contemporary Poland and organized various forms of group life.